Análisis del crecimiento del Network Marketing e identificación de los factores que podrían condicionar el éxito de una persona en el negocio multinivel en el mercado colombiano (2015)
In the world there are some companies that aims to bring consumers to be the ones who distribute their products, providing the opportunity to earn a profit by marketing as well as the opportunity to start building a network of partners, that engaged in distributing the same products and generate commissions from the sales of all equipment, this system is called Network Marketing, the purpose of this research is to investigate the characteristics of these distribution systems, beginning to understand the definition of multi-level business, according some of the most outstanding authors on the topic as Robert Kiyosaki and Richard Poe. Then enter in the analysis of the direct selling model in the US economy, which has the largest market share of MLM (Multi-Level Marketing). In this way opens a context for field work consisting of two parts, first know the perspective of the population of the municipality of Armenia, Quindío about MLM, what will be done through interviews; and the second part of participatory observation, developing activities such as Networker in the city of Armenia, in order to identify firsthand, what are the factors for the success of a person in a Network Marketing Business.